The mutational landscape and prognostic indicators of pseudomyxoma peritonei originating from the ovary. Issue 8 (11th January 2021) - Wang, Bing; Yao, Jianfei; Ma, Ruiqing; Liu, Danni; Lu, Yiyan; Shi, Guanjun; An, Lubiao; Xia, Ao; Chen, Feng; Pang, Shaojun; Zhai, Xichao; Liu, Guifeng; et al.
Abstract: Pseudomyxoma peritonei (PMP) is a rare disorder with unique pathological and genetic changes. Although several studies have reported the clinical features and mutational changes of PMP that originates from the appendix, few studies on PMP originating from the ovary have been reported due to its extreme rarity. In order to characterize the somatic mutational landscape and to investigate the prognosis predicting factors of ovary‐originating PMP, we examined 830 cases of PMP and identified 16 patients with PMP that originated from the ovary. Whole‐exome sequencing (WES) was performed on 12 cases using formalin‐fixed, paraffin‐embedded (FFPE) tissue samples. We found that 25% (3/12) of the patients carried mutations in cancer driver genes, including TP53, ATM and SETD2, and 16.7% (2/12) of the patients carried mutations in cancer driver genes, including ATRX, EP300, FGFR2, KRAS, NOCR1 and RB1. The MUC16 (58.33%), BSN (41.67%), PCNT (41.67%), PPP2R5A (41.67%), PRSS36 (41.67%), PTPRK (41.67%) and SBF1 (41.67%) genes presented the highest mutational frequencies. The PI3K‐Akt signaling pathway, human papillomavirus infection pathway, cell skeleton, cell adhesion, and extracellular matrix and membrane proteins were the major pathways or functions that were affected. Patients were followed up to 174 months (median: 48.26 months). The 5‐year OS rate for all patients was 71.2% and the median OS was not reached. PTPRK mutations, presurgical CA199 level, completeness of cytoreduction (CCR) and peritoneal cancer index (PCI) were identified as potential predictive factors for patient survival. In conclusion, the mutational landscape for ovary‐originating PMP was revealed and exhibited unique features distinct from appendix‐originating PMP. PTPRK, CA199, CCR and PCI may predict patient survival. Abstract : What's new? Pseudonymous peritoneum (PMP), an exceedingly rare malignancy, typically originates from tumors in the appendix. While PMP may also originate from the ovary, less is known about the molecular landscape of this form of the disease. Here, investigation of genetic and serum protein marker alterations in patient samples uncovered multiple mutations in cancer driver genes, including TP53 and ATM, in ovary‐originating PMP patients. Meanwhile, levels of protein markers, including CA125, CEA, and CA199, were elevated in serum and ascites fluid. Genetic and protein marker alterations were related to patient survival, which was further correlated with the clinically relevant peritoneal cancer index.